Prevalence and Impact of Food Allergies Among Jordanian Schoolchildren: A Comprehensive Analysis of Parent-Reported Data and Associated Atopic Conditions - Nour Yousef; Raghda O’leimat; Mohammad Abdelraheem; Eyad Altamimi (International Journal of Pediatrics)
Conclusion: This study emphasizes the significance of considering persuasive food allergy (FA) data in addition to parent-reported information. The findings highlight the considerable burden of food allergies and their relationship with other atopic disorders. Comprehensive management strategies and further research to elucidate the underlying causes of food allergies are necessary.